2019
DOI: 10.1097/meg.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of anticoagulation therapy for Pyrrolizidine alkaloids-induced hepatic sinusoidal obstruction syndrome: a retrospective multicenter cohort study

Abstract: Aim Pyrrolizidine alkaloids-induced hepatic sinusoidal obstruction syndrome(PA-HSOS) has been reported to have high mortality. We evaluated the efficacy and safety of anticoagulation therapy for the patients with PA-HSOS. Methods We collected clinical data on 249 PA-HSOS patients from January 2012 to December 2017 at four tertiary care hospitals. Among them, 151 patients received anticoagulation therapy, and 98 patients received supportive treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…However, this guideline has no clear recommendation on the TBIL level for TIPS. Peng et al 15 observed the efficacy of TIPS in the treatment of PA-HSOS patients, but did not study the timing of TIPS intervention, and did not show the serum TBIL level of patients before TIPS. In our study, 4 patients received TIPS for refractory ascites associated with portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, this guideline has no clear recommendation on the TBIL level for TIPS. Peng et al 15 observed the efficacy of TIPS in the treatment of PA-HSOS patients, but did not study the timing of TIPS intervention, and did not show the serum TBIL level of patients before TIPS. In our study, 4 patients received TIPS for refractory ascites associated with portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a diagnostic test with a power of 0.80 and an alpha of 0.05. Based on the fact that the overall complete remission rate was 60.9% in PA-HSOS patients receiving anticoagulation therapy [ 9 ], the prevalence (no response to anticoagulation rate) in our study was 0.391. With a Se1 (alternative sensitivity) of 0.95, a Sp1 (alternative specificity) of 0.90, both Se0 (null sensitivity) and Sp0 (null specificity) equivalent to 0.75, the minimum sample size required was 89 cases according to Power Analysis and Sample Size (PASS) (NCSS statistical software, Kaysville, Utah, USA) version 15.0.…”
Section: Methodsmentioning
confidence: 96%
“…Research has shown that PA-HSOS patients with mild or moderate severity grades, based on the severity criteria for sinusoidal obstruction syndrome published by the European Blood and Bone Marrow Transplantation (EBMT) Collaboration Group in 2016 [ 8 ], are more likely to benefit from anticoagulation therapy. However, 30.17% of mild patients and 33.82% of moderate patients were reported to be unresponsive [ 9 ]. The severity criteria put forward by the EBMT Collaboration Group is associated with certain shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…PAs are naturally inactive components and safe. They are metabolically triggered in the body by hepatic enzymes, specially CYP3A and CYP2B isoforms (117). Studies showed that toxicity varies according to the chemical structure of an individual PA in-vitro (118)(119)(120).…”
Section: Phytochemicals and Anti-inflammatory Properties Of Symphytum...mentioning
confidence: 99%